Impaired fasting glucose levels among perinatally HIV-infected adolescents and youths in Dar es Salaam, Tanzania - Nkinda, Lilian; Buberwa, Eliud; Memiah, Peter; Ntagalinda, Alieth; George, Martin; Msafiri, Frank; Joachim, Agricola; Majigo, Mtebe; Ramaiya, Kaushik; Sunguya, Bruno (Frontiers in Endocrinology, 2022)
Objective This study assessed impaired fasting glucose and associated factors among perinatally HIV-infected adolescents and youths in Dar es salaam Tanzania. Background Impaired fasting glucose is a marker of heightened risk for developing type 2 diabetes among perinatally HIV-infected individuals. Therefore, identifying individuals at this stage is crucial to enable early intervention. Therefore, we assessed impaired fasting glucose (IFG) and associated factors among perinatally HIV-infected population in Dar es salaam Tanzania. Methods A cross-sectional study was conducted among 152 adolescents and youth attending HIV clinic at Muhimbili National Hospital and Infectious Disease Centre from July to August 2020. Fasting blood glucose (>8 hours) was measured using one-touch selects LifeScan, CA, USA. We also examined C-Reactive Protein and interleukin-6 inflammatory biomarkers in relation to impaired fasting glucose (IFG). Associations between categorical variables were explored using Chi-square, and poison regression with robust variance was used to calculate the prevalence ratios. Results Of the 152 participants, the majority were male (n=83[54.6%]), and the median age was 15(14-18) years. Overweight or obesity was prevalent in 16.4%, while more than one in ten (13.2%) had high blood pressure (≥149/90mmHg). All participants were on antiretroviral therapy (ART); 46% had used medication for over ten years, and about one in three had poor medication adherence. Among the recruited participants, 29% had impaired fasting glucose. The odds of IFG were two times higher in males compared to females (PR, 2.07, 95% CI 1.19 -3.59 p=0.001). Moreover, we found with every increase of Interleukin 6 biomarker there was a 1.01 probability increase of impaired fasting glucose (PR, 1.01, 95% CI 1.00 – 1.02 p=0.003). Conclusion About one in three perinatally HIV-infected youths had impaired fasting glucose in Dar es Salaam, Tanzania, with males bearing the biggest brunt. Moreover, with every increase of 1.101 of the probability of having IFG increased. This calls for urgent measures to interrupt the progression to diabetes disease and prevent the dual burden of disease for this uniquely challenged population.